Análise da incorporação do resíduo do beneficiamento de rochas ornamentais tratado termicamente na composição do cimento Portland - Rodrigues, Larissa Helena Carnielli Howat (2018)
In Brazil, especially in the state of Espirito Santo, ornamental rock mining reaches one of the main economic activities, generating tons of waste from this beneficiation process. The objective of this work was to evaluate the potential of the thermally treated ornamental rock residue as a partial replacement material in the Portland cement production. For the analysis of the properties of Portland cement produced in this work called CP II R, the tests of fineness, specific surface, expandability, setting time, mechanical strength and chemical analyzes were carried out by the Brazilian Association of Technical Standards - ABNT, and complementary mineralogical and microstructural tests. The residual substitution contents were 6%, 10% and 14% by mass of clinker, using as reference the mixtures of 0% and CP II Z-32 marketed. The CP II R in all contents of the residue presented values that met the criterion of the standard making possible the use of RBROTT in the composite Portland Cement composition. Physically it presented fine particles with chemical composition rich in silica and alumina. The mechanical results indicated a resistance greater than 65MPa at 120 days and the complementary analyzes demonstrated cohesive matrices with the observance of all elements of the phases of hydration. The CP II R-14% was the optimum content found in this research.